A comparison of the accuracy of the cervical vertebrae maturation stage method and Demirjian’s method on mandibular length growth - Alfira Putriana Dewi; Seno Pradopo; Sindy Cornelia Nelwan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Malocclusion is one of the most familiar dental problems, with a high prevalence among the population. Understanding the patient’s craniofacial growth and development is crucial in diagnosis, as are the planning and subsequent success of the treatment. Malocclusion needs to be treated early to optimise the outcome achieved by the treatment. One of the most common types of malocclusions observed in clinics is crowding. The craniofacial bone relevant to the treatment of crowding is the mandible, defined as the mandibular length from the condylion to gnathion areas. When planning treatment, clinicians may experience difficulties in determining the biological age of patient, particularly when supporting diagnostic tools are not available. The indicators of biological age can be observed by the assessment of bone maturation using the cervical vertebrae maturation (CVM) method and by the analysis of tooth maturation using Demirjian’s method. However, limited studies are available regarding the accuracy of these methods as diagnostic tools. Purpose: This study aims to analyse the accuracy of the CVM method compared with Demirjian’s method concerning mandibular length growth. Methods: An analytic research method and a cross-sectional design are employed. The research sample comprised 50 lateral cephalometric and panoramic photos of children aged 8-16 years. Data were collected by analysing the maturity level of the cervical vertebrae and the teeth, and measuring the mandible length of the children in the photos. The statistical test used was the Wilcoxon test. Results: The results of the Wilcoxon test for the asymptotic sign had a p-value of 0.116 > 0.05, indicating no significant difference between the CVM and Demirjian methods. Conclusion: Both of the methods noted above yielded equally accurate results for determining mandibular length growth.